2018
DOI: 10.1007/978-3-319-98788-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Animal Models Designed for Investigating Ethanol Metabolism, Toxicity and Cancer

Abstract: Excessive consumption of alcohol is a leading cause of lifestyle-induced morbidity and mortality worldwide. Although long-term alcohol abuse has been shown to be detrimental to the liver, brain and many other organs, our understanding of the exact molecular mechanisms by which this occurs is still limited. In tissues, ethanol is metabolized to acetaldehyde (mainly by alcohol dehydrogenase and cytochrome p450 2E1) and subsequently to acetic acid by aldehyde dehydrogenases. Intracellular generation of free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Some of these symptoms can be attributed to differentiation deficits in the cerebellar cortex and subsequent impairment in cerebellar coordinative controls on cognitive functions through the cerebello-cerebral loops. Ethanol is metabolized to acetaldehyde by alcohol dehydrogenase and cytochrome p450 2E1 and subsequently to acetic acid by aldehyde dehydrogenases [10]. Intracellular generation of free radicals and depletion of the antioxidant glutathione are vital steps in the cellular pathogenic events caused by ethanol [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these symptoms can be attributed to differentiation deficits in the cerebellar cortex and subsequent impairment in cerebellar coordinative controls on cognitive functions through the cerebello-cerebral loops. Ethanol is metabolized to acetaldehyde by alcohol dehydrogenase and cytochrome p450 2E1 and subsequently to acetic acid by aldehyde dehydrogenases [10]. Intracellular generation of free radicals and depletion of the antioxidant glutathione are vital steps in the cellular pathogenic events caused by ethanol [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol is metabolized to acetaldehyde by alcohol dehydrogenase and cytochrome p450 2E1 and subsequently to acetic acid by aldehyde dehydrogenases [10]. Intracellular generation of free radicals and depletion of the antioxidant glutathione are vital steps in the cellular pathogenic events caused by ethanol [10]. In addition to such a classic view, recent studies using various animal models have shown diverse pathophysiological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon ingestion, alcohol is metabolized to acetaldehyde by alcohol dehydrogenase and cytochrome enzymes and eventually to acetic acid [37]. Throughout these steps, free radicals are generated, and cells are predisposed to oxidative stress, leading to cellular pathology [38]. Various studies have shown that alcohol exposure impairs mitochondrial function and elevates free radical production [39].…”
Section: Discussionmentioning
confidence: 99%